Morphology of extensor digitorum longus of Wistar rats after remobilization by vibratory platform - Camilo, Izabela Rodrigues; Wutzke, Maria Luiza Serradourada; Costa, Rose Meire; Bertolini, Gladson Ricardo Flor; Ribeiro, Lucinéia de Fátima Chasko (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
Introduction. In exercise, vibrations are performed in order to produce rapid and short changes in muscle length. These changes are detected by sensory receptors, in response try to dampen the vibratory waves through a modulation of muscle stiffness. However, its effects on the morphology of muscle tissue are still not fully established, especially after long periods of immobilization. Aim. To compare the effects of the vibratory platform on the remobilization of the extensor digitorum longus (EDL) muscle of Wistar rats with free remobilization. Material and methods. 20 rats were divided into: CG (Control), IG (immobilized), IFG (immobilization and free remobilization), IPG (immobilization and remobilization with vibratory platform). The immobilization was performed on the pelvic limb for 15 days. The remobilization with vibratory platform was done for 10 minutes daily, for 2 weeks. The EDL was processed for histological analysis of cross-sections. Results. The area, larger diameter, smaller diameter and fiber density of the EDL muscle of GI presented significant alteration when opposed to CG, IFG and IPG. The density of nuclei of the EDL muscle of IG presented a significant increase when opposed to the others, and IPG also presented a significant increase when compared to CG. Conclusion. The morphology and morphometry of the EDL muscle tissue were affected, and both free and vibration platform remobilization re-established the morphological aspects of the muscle fiber, without significant differences between the methods.
Keywords: immobilization; skeletal muscle; vibration